2002
DOI: 10.1080/09546630252775171
|View full text |Cite
|
Sign up to set email alerts
|

An open, randomized, comparative study of oral fluconazole, itraconazole and terbinafine therapy in onychomycosis

Abstract: This comparative study of systemic fluconazole, itraconazole and terbinafine showed that all three drugs were effective and safe in the treatment of onychomycosis. However, fluconazole, at these doses and treatment durations, was the least effective. With regard to cost-effectiveness, side effects and the cure rates, terbinafine could be the drug of choice in the short-term treatment of toenail onychomycosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 36 publications
0
19
0
1
Order By: Relevance
“…in their study in patients with onychomycosis reported 81.3% clinical cure rate and 75% mycological cure rate with terbinafine. [19] In our survey, terbinafine given for 4 weeks was found to be most effective treatment strategy against superficial dermatophytosis.…”
Section: Discussionmentioning
confidence: 94%
“…in their study in patients with onychomycosis reported 81.3% clinical cure rate and 75% mycological cure rate with terbinafine. [19] In our survey, terbinafine given for 4 weeks was found to be most effective treatment strategy against superficial dermatophytosis.…”
Section: Discussionmentioning
confidence: 94%
“…Clinical cure rates (21%-38% vs 67%-81%), mycological cure rates (31%-51% vs 75-89%) and overall effi cacy (31% vs 62%) were inferior in fl uconazole treated patients. 135,142 Despite reasonable effi cacy rates, the results of numerous trials indicate that a substantial fraction of onychomycosis patients treated with terbinafi ne remain uncured at the end Terbinafi ne in dermatophytoses of treatment. Consequently several investigations have attempted to address whether additional intrinsic or extrinsic factors infl uence treatment response.…”
Section: Onychomycosismentioning
confidence: 99%
“…In the treatment of distal and lateral subungual onychomycosis restricted to dermatophytes, no appreciable difference was observed between itraconazole (400 mg/day one week "on" three weeks "off ") and terbinafi ne (mycological cure rates: 75%-90% vs 76%-87%, clinical cure rates 53%-82% vs 50%-79%). [135][136][137][138] Not surprisingly, itraconazole demonstrated superior cure rates among the non-dermatophyte moulds (62% vs 44%) and Candida species (92% vs 40%). 138 These studies are contradicted by a large multi-national trial wherein mycological cure rates at 18 months were significantly greater with terbinafine (76%-80%) than observed with pulse-dose itraconazole (38%-49%).…”
Section: Onychomycosismentioning
confidence: 99%
“…Less than 50% involvement was defined as mild, 51-75% involvement as moderate, and above 75% as severe [16,17,18]. According to this classification, a mild 10% involvement and 50% involvement are in the same category, despite the fact that 10% involvement is much easier to treat and better results are achieved.…”
Section: Using a Precise Scoring Systemmentioning
confidence: 99%